Upgrading the quality of mixed recycled aggregates from construction and demolition waste by using near-infrared sorting technology. (30th January 2015) - Vegas, Iñigo; Broos, Kris; Nielsen, Peter; Lambertz, Oliver; Lisbona, Amaia
Highlights: Near Infrared sorting technologies favour selective removal of impurities. The quality of mixed recycled aggregates is upgraded by using NIR sorting solutions. Advanced sorting solutions can achieve more valuable recycled aggregates. Abstract: Recycled aggregates of high-purity, guaranteeing optimal technical and environmental performance, are required for high-grade construction applications such as concrete. The main problem constituents causing a decrease in the quality of recycled aggregates to be used in high grade applications are: organic material, gypsum and autoclaved aerated concrete (AAC). This paper studies the potential of Near Infrared (NIR) sorting technology to improve the quality of mixed recycled aggregates. Tests were carried out by using samples of mixed recycled aggregates collected in different EU countries (Germany, Sweden, Spain and Italy). Constituents, total sulphur content, acid soluble sulphates, total heavy metals and metal leaching were determined before and after the use of the NIR sorting technology. The results clearly indicate that the problematic fractions (organic material, gypsum and AAC) in the mixed recycled aggregates can be significantly reduced or even eliminated during the NIR sorting treatment, boosting a greater use of recycled aggregates in high grade applications such as concrete manufacturing.